Influence of temperature on the properties of the xylanolytic enzymes of the thermotolerant fungus Aspergillus phoenicis - Rizzatti, ACS; Sandrim, V. C.; Jorge, J.; Terenzi, H. F.; Polizeli, MDTM (Springer, 2004)
This study reports on the effects of growth temperature on the secretion and some properties of the xylanase and beta-xylosidase activities produced by a thermotolerant Aspergillus phoenicis. Marked differences were observed when the organism was grown on xylan-supplemented medium at 25 degreesC or 42 degreesC. Production of xylanolytic enzymes reached maximum levels after 72 h of growth at 42 degreesC; and levels were three- to five-fold higher than at 25 degreesC. Secretion of xylanase and beta-xylosidase was also strongly stimulated at the higher temperature. The optimal temperature was 85 degreesC for extracellular and 90 degreesC for intracellular beta-xylosidase activity, independent of the growth temperature. The optimum temperature for extracellular xylanase increased from 50 degreesC to 55 degreesC when the fungus was cultivated at 42 degreesC. At the higher temperature, the xylanolytic enzymes produced by A. phoenicis showed increased thermo stability, with changes in the profiles of pH optima. The chromatographic profiles were distinct when samples obtained from cultures grown at different temperatures were eluted from DEAE-cellulose and Biogel P-60 columns.
Keywords: aspergillus phoenicis; thermostability; growth temperature; xylanase; beta-d-xylosidase